Oral administration of lysozyme protects against injury of ileum via modulating gut microbiota dysbiosis after severe traumatic brain injury - Yang, Weijian; Xi, Caihua; Yao, Haijun; Yuan, Qiang; Zhang, Jun; Chen, Qifang; Wu, Gang; Hu, Jin (Frontiers in Cellular and Infection Microbiology, 2024)
Objective The current study sought to clarify the role of lysozyme-regulated gut microbiota and explored the potential therapeutic effects of lysozyme on ileum injury induced by severe traumatic brain injury (sTBI) and bacterial pneumonia in vivo and in vitro experiments. Methods Male 6–8-week-old specific pathogen-free (SPF) C57BL/6 mice were randomly divided into Normal group (N), Sham group (S), sTBI group (T), sTBI + or Lysozyme-treated group (L), Normal + Lysozyme group (NL) and Sham group + Lysozyme group (SL). At the day 7 after establishment of the model, mice were anesthetized and the samples were collected. The microbiota in lungs and fresh contents of the ileocecum were analyzed. Lungs and distal ileum were used to detect the degree of injury. The number of Paneth cells and the expression level of lysozyme were assessed. The bacterial translocation was determined. Intestinal organoids culture and co-coculture system was used to test whether lysozyme remodels the intestinal barrier through the gut microbiota. Results After oral administration of lysozyme, the intestinal microbiota is rebalanced, the composition of lung microbiota is restored, and translocation of intestinal bacteria is mitigated. Lysozyme administration reinstates lysozyme expression in Paneth cells, thereby reducing intestinal permeability, pathological score, apoptosis rate, and inflammation levels. The gut microbiota, including Oscillospira, Ruminococcus, Alistipes, Butyricicoccus, and Lactobacillus, play a crucial role in regulating and improving intestinal barrier damage and modulating Paneth cells in lysozyme-treated mice. A co-culture system comprising intestinal organoids and brain-derived proteins (BP), which demonstrated that the BP effectively downregulated the expression of lysozyme in intestinal organoids. However, supplementation of lysozyme to this co-culture system failed to restore its expression in intestinal organoids. Conclusion The present study unveiled a virtuous cycle whereby oral administration of lysozyme restores Paneth cell’s function, mitigates intestinal injury and bacterial translocation through the remodeling of gut microbiota.